The Influence of Emotional Intelligence, Learning Facilities, Parenting Styles, and Peer Environment on the Learning Outcomes of Economics Subjects of Grade XI Students of SMA N 1 Rambatan with Learning Discipline as an Intervening Variable - Nelvia Sri Winda; Jolianis; Desi Areva (Journal of Classroom Action Research, 2025)
This study aims to analyze the influence of emotional intelligence, learning facilities, parenting styles, and peer environment on learning discipline and their impact on student learning outcomes. The research method used is associative with a quantitative approach. The study population was all eleventh-grade students at SMAN 1 Rambatan, with a sample of 76 students drawn using stratified random sampling based on parental education level. Data collection was conducted using a closed-ended questionnaire, while data analysis used path analysis and a t-test to test hypotheses. The results indicate that emotional intelligence, learning facilities, parenting styles, and peer environment significantly influence learning discipline. Furthermore, these five variables, along with learning discipline, also significantly influence student learning outcomes. The magnitude of the influence varied based on parental education level, with parenting styles having the largest contribution to learning outcomes in the low-education group (27.4%), while learning facilities contributed the most in the high-education group (11.8%). This study concludes that learning discipline and learning outcomes are significantly influenced by both internal and external factors, with the strength of the influence varying depending on parental educational background.